CEO Education from Reputable University and ESG Disclosure: Evidence from Indonesia - Ulinnuha, Kukuh Shafira; Harymawan, Iman; Aini, Siti Nur (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2024)
This study aims to examine the influence of CEO educational background, specifically MBA and engineering degrees gained from reputable universities, on environmental, social, and governance disclosure. The sample used in this study consists of 332 companies out of the total population of 407 listed companies on the Indonesia Stock Exchange that disclosed sustainability reports during the period from 2016 to 2020. The analysis was conducted using multiple linear regression. The findings of this study reveal that CEOs with MBA and engineering degrees gained from reputable universities, based on the QS world university ranking, significantly and positively influence ESG disclosure. This research contributes to the literature on CEO characteristics, particularly their educational background with specific degrees like MBA and engineering, and their impact on ESG disclosure. For policymakers, these findings highlight the importance of considering the educational background of the CEO in the selection and training process, as well as its potential implications for ESG disclosure regulations.